2001
DOI: 10.1123/ijsnem.11.4.406
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Carbohydrate and Milk-Based Beverages on Muscle Damage and Glycogen Following Exercise

Abstract: This study examined effects of carbohydrate (CHO), milk-based carbohydrate-protein (CHO-PRO), or placebo (P) beverages on glycogen resynthesis, muscle damage, inflammation, and muscle function following eccentric resistance exercise. Untrained males performed a cycling exercise to reduce muscle glycogen 12 hours prior to performance of 100 eccentric quadriceps contractions at 120% of 1-RM (day 1) and drank CHO (n = 8), CHO-PRO (n = 9; 5 kcal/kg), or P (n = 9) immediately and 2 hours post-exercise. At 3 hours p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 0 publications
4
51
1
1
Order By: Relevance
“…Furthermore, Tarnopolsky and coworkers 48 found significantly higher glycogen concentrations (4 hours post-exercise) after ingesting a CHO-only (1 g CHO/kg BW/serving) compared with an isocaloric CHO-protein (0.75 g CHO + 0.1 g protein + 0.02 g fat/kg BW/serving) supplement after a glycogen-depleting exercise protocol. These results are supported Wojcik and co-workers, 56 and may suggest that insulin is not the rate-limiting factor for muscle glycogen synthesis when the overall rate of CHO intake is high (> 1 g CHO/kg BW/hour).…”
Section: Effect Of Combining Cho and Protein On Muscle Glycogen Storagesupporting
confidence: 79%
“…Furthermore, Tarnopolsky and coworkers 48 found significantly higher glycogen concentrations (4 hours post-exercise) after ingesting a CHO-only (1 g CHO/kg BW/serving) compared with an isocaloric CHO-protein (0.75 g CHO + 0.1 g protein + 0.02 g fat/kg BW/serving) supplement after a glycogen-depleting exercise protocol. These results are supported Wojcik and co-workers, 56 and may suggest that insulin is not the rate-limiting factor for muscle glycogen synthesis when the overall rate of CHO intake is high (> 1 g CHO/kg BW/hour).…”
Section: Effect Of Combining Cho and Protein On Muscle Glycogen Storagesupporting
confidence: 79%
“…Os autores sugeriram que o maior nível de insulina poderia aumentar a síntese de glicogênio muscular. Alguns autores demonstraram que a inclusão de proteínas na refeição pós-esforço acelera a reposição do glicogênio muscular 46 , mas nenhum efeito dessa estratégia foi observado por Wojcik et al 47 , comparando suplementação de carboidrato com proteína + carboidrato. Portanto, a eficácia da ingestão de proteínas em conjunto com carboidratos, sobre a reposição do glicogênio muscular, é uma questão ainda não esclarecida.…”
Section: Reposição Do Glicogênio Muscular E Estratégias De Supercompeunclassified
“…Previous investigations administering milk following exercise have looked at muscle protein synthesis (Elliot et al 2006), muscle function and glycogen synthesis (Wojcik et al 2001). Karp et al (2006) reported a greater restoration of exercise capacity following the ingestion of chocolateXavoured milk, when compared to a CHO replacement solution of a similar macronutrient composition.…”
Section: Introductionmentioning
confidence: 99%